2009
DOI: 10.1002/jlcr.1597
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro evaluation of 18F‐labelled di‐ and tri(ethylene glycol) metomidate esters

Abstract: By replacing the alkyl chain in a metomidate ester with 18 F]fluorination reactions using conventional and microwave heating. Organ distribution, frozen section autoradiography and metabolite analysis were performed. The decay-corrected radiochemical yields of 1 and 2 were 2678 and 2378%, respectively, when they were prepared using conventional heating. By performing microwave heating, the reaction time could be decreased and the yields of analogues 1 and 2 could be increased to 57712 and 51718%, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…3839 These investigators found that the ethyl ester was slightly more stable in vivo than the diethylene glycol ester, and that the difference between stability of the triethylene and diethylene glycol esters was minimal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3839 These investigators found that the ethyl ester was slightly more stable in vivo than the diethylene glycol ester, and that the difference between stability of the triethylene and diethylene glycol esters was minimal.…”
Section: Resultsmentioning
confidence: 99%
“…These investigators also measured the metabolic stability of the diethylene and triethylene glycol esters of metomidate in rats and found that only 2% of the diethylene glycol ester remained intact at 30 min after injection compared to 6% of the triethylene glycol ester. 39 In combination, these results suggest, somewhat unexpectedly, that changing the ester group has minimal impact on the in vivo stability of these compounds.…”
Section: ■ Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…11 C-Labelled analog of harmine was used to detect the high expression of MAO-A in neuroendocrine gastroenteropancreatic tumor. 10 18 F-Labelled analogs of these tracers, metomidate, 11,12 vorozole 13 and harmine 14 have recently been developed and evaluated as PET tracers. The previous papers described the syntheses on the semi-automated platform Synthia 15 developed at Uppsala University PET center.…”
Section: Ethyl 1-[(1r)-1-phenylethyl]-1h-imidazole-5-carboxylate (Etomentioning
confidence: 99%
“…But most improvements involve the introduction of automated procedures, as in the labelling of fluorodeoxyglucose, 131,132 fluoro-L-DOPA, 133 16a-[F 18 ]fluoroestradiol, 134 [F 18 ]fluoroethylcholine, 135 [F 18 ]fluorotetracosactide, 136 9-(4-[F 18 ]fluoro-3-hydroxymethylbutyl)guanine, 137 substituted nitroimidazoles, 138 a range of fluorinated arabinofuranosyluracils 139 and even sodium [F 18 ]fluoride 140 itself. Other molecules labelled with fluorine-18 have included N-succinimidyl-4-fluorobenzoate, 141 ethyleneglycol metomidate esters, 142 tyrosine 143 and cysteine 144 derivatives for tumour imaging, flumazenil, 145,146 2-fluoro-3-(hex-5-ynyloxy)pyridine 147 and 2 0 fluoro-5-iodo-1-b-D-arabinofuranosylcytosine, 148 both for use in protein labelling, as well as [F 18 ]altanserin 149 for plasma metabolite studies, N,N-dimethyl-2-(2-amino-4-fluorophenylthio)benzylamine, 150 for serotonin imaging and the muscarinic M2 radiopharmaceutical, FP-TZTP. 151 Phosphorus (P 32 & P 33 ) and sulfur (S 35 )…”
Section: Carbon (C 11 and C 14 )mentioning
confidence: 99%